Zoogeodraphical and historical faunistic characteristic of the spieces of dragon-fly of the Aeshnidae family of Mineral Water of Caucasus - Kh. A. Ketenchiev; L. K. Abrekova (Юг России: экология, развитие, 2015)
In this work the materials on zoogeographical and geographics distribution of the dragon-flies of Mineral Waters of Caucasus are given.